Border tourism behavior in increasing the number of tourist visits in Batam - Pristiwasa, I Wayan Thariqy Kawakibi; Octavia, Kanzila Eka (Jurnal Pariwisata Pesona, 2025)
Batam City is one of Indonesia's border areas that has great potential as a cross-country tourist destination. This study aims to analyze the behavior of cross-border tourists visiting Batam City, Indonesia, primarily from Singapore and Malaysia. The research focuses on four main variables: motivation, perceived quality, perceived risk, and tourist attitudes. The study employed a quantitative method by distributing questionnaires to 250 respondents across five main entry points: Batam Center Port, Harbour Bay, Sekupang, Waterfront City, and Nongsapura. Data analysis was conducted using cross-tabulation and chi-square tests. The findings revealed that prestige motivation, perceived price quality, health risks, and responsible attitudes were the dominant factors influencing tourist behavior. The implications suggest that local governments and tourism stakeholders should improve service quality and tourism products to enhance Batam’s competitiveness as a safe and attractive cross-border destination.